Ibrahim Muminov’s Legal and Political Views on the Formation of Uzbek Philosophy - Yadgarov Begzod (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article presents a detailed analysis of the legal and political views of the Uzbek philosopher Ibrohim Muminov and their role in the formation of Uzbek philosophy. Muminov's philosophical views, including his social and political views, influenced the development of Uzbek society. In his legal and political ideas, he put forward such important social values ​​as human rights, justice, democracy and freedom. The article analyzes Muminov's political and legal views and shows how they influenced Uzbek thinking, social, political and legal systems of society.